Pemberdayaan Sosial Ekonomi Pedagang Makanan di Kelurahan Cikawao Kecamatan Lengkong Kota Bandung - Pramiarsih, Euis Eka; Purnomo, Hadi; Kunyati, Siti Anah (Jurnal Pengabdian Tri Bhakti, 2025)
Micro Enterprises are the largest absorbers of labor, providing employment for millions of people, especially in the informal sector. Cikawao, Lengkong, Bandung is a densely populated urban area, with diverse economic statuses, offices, education, culinary delights, making it an attraction for business people to carry out various activities and micro enterprises with various types of businesses have emerged, based on data from micro enterprises in Lengkong district as many as 360 MSMEs. The problems identified are: 1) Low product quality and food diversification to be marketed; 2) Limited product marketing; 3) Business group organization has not yet been established, 4) Difficulty obtaining business capital assistance; 5) Limited infrastructure for sales. The methods used in PKM are: 1) Improving product quality and diversifying food products through training, 2) Expanding food product marketing, 3) Organizing groups through FGDs, 4) Providing loans from Unla Peduli to obtain business capital, 5) Obtaining business facilities for stakeholders. The results of community service activities: 1) Increasing the number of products produced by food businesses, 2) Expanding marketing by connecting with institutions in need of food, especially for free Friday Blessing meals, 3) Establishing a food business community called "Kelompok Usaha Maju Bersama" (Joint Business Group), 4) Assisting businesses in developing funding proposals, 5) Obtaining business facilities for stakeholders.